Factors influencing the utilization of the Modern Family Planning (MFP) method under the National Health Insurance in Indonesia: An analysis of the 2017 IDHS - Maretalinia, Maretalinia; Rusmitasari, Heni; Supriatin, Supriatin; Amaliah, Lili; Sukmawati, Ellyzabeth; Suwarni, Linda (YCAB Publisher & IAKMI SULTRA, 2023)
Background: Indonesia recently implemented a National Health Insurance program while simultaneously grappling with the challenge of unmet family planning needs. Objective: This study aimed to examine the correlation between health insurance ownership and the utilization of family planning methods among married/in-union women in Indonesia. Methods: This study employed secondary data analysis using the 2017 Indonesian Demography and Health Survey (IDHS). The analysis included a sample of 18,411 married/in-union women. Univariate, bivariate (Chi-square test), and multivariate (binary logistic regression) analyses were conducted to examine the relationship between health insurance ownership and the utilization of family planning methods. Results: The analysis revealed that a small proportion of individuals with health insurance utilized family planning services. Several factors were found to be associated with the utilization of family planning services, including ownership of health insurance, women's age, family planning decision-maker, socioeconomic status (as measured by being in the richest quintile), and higher education attainment. Conclusion: The findings of this study provide important insights for policymakers and public health practitioners regarding the integration of national health insurance programs and family planning initiatives in Indonesia. It is crucial to address the low utilization rate of family planning services among those with health insurance. Future research should focus on fostering collaboration among all stakeholders to promote comprehensive education on freely accessible contraceptive methods, aiming to bridge the gap between policy implementation and effective utilization of family planning services.